Dual cannabis and alcohol use disorders in young adults: Problems magnified. Issue 4 (1st October 2016) - Hayaki, Jumi; Anderson, Bradley J.; Stein, Michael D.
ABSTRACT: Background : Alcohol and marijuana are the 2 most commonly used substances among young adults. The present study examines whether having 2 DSM-5 ( Diagnostic and Statistical Manual of Mental Disorders, 5th Edition ) diagnoses (alcohol and cannabis) is associated with greater problems than having 1 (alcohol or cannabis) diagnosis. Methods : Participants were 307 young adults (18–25 years) from the community who met criteria for DSM-5 alcohol use disorder (AUD), cannabis use disorder (CUD), or both (dual use disorder [DUD]). Participants reported alcohol and marijuana use in the past 90 days (Timeline Follow-Back), alcohol problems (Short Inventory of Problems), and marijuana problems (Marijuana Problems Scale). Results : Eighty-four participants (27.4%) met criteria for AUD, 107 (34.9%) met criteria for CUD, and 116 (37.8%) met criteria for DUD. In multivariate analyses, the DUD group reported greater alcohol use frequency and more alcohol problems than the CUD-only group but not the AUD-only group. However, DUD individuals reported greater drinking intensity than singly diagnosed individuals. Those with DUD reported a greater proportion of marijuana consumption days than the AUD-only group but not the CUD-only group. However, DUD individuals reported more marijuana problems than both singly diagnosed groups. Conclusions : Results show that the concurrent presence of both DSM-5 AUD and CUD is associated with heavier drinking patterns and greater marijuana problems than disordered use of either substance alone, thus affirming the magnified severity of alcohol and marijuana use that accompanies dual DSM-5 alcohol and marijuana use disorders.